RANCANG BANGUN ALAT PRESS TEPUNG SAGU - Dandy Dwiky Yusuf; Yus Witdarko; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2021)
The purpose of this research is to design a press machine for sago flour that is in accordance with the demand for efficient sago flour production in terms of energy and time without reducing the quality of the sago flour. This research consists of; preparation stage (tool designs, proposal, provision of tools and materials includes sago flour). The second stage is making a sago flour press machine. The last stage is testing the machine, taking sago flour sample data to see the water content of sago flour and pressing time, and calculating the performance of the sago flour press on the water content of the sago flour produced. This manual sago flour press tool uses the method of a screwed iron sideways (horizontally). Based on the research, the following results were obtained: a press with a box frame with size of 50 x 50 cm, a frame leg height of 30 cm, a press plate thickness of 2 cm, a large iron tray hole with 3 cm of length and 0.5 cm of width can reduce the average content water content of 20 kg sago flour as much as 38.28% for 10 minutes. The average water content of sago flour produced after the pressing process is 22.30%. From the results obtained, this manual sago flour press can work well during the pressing process and can reduce the water content of sago flour efficiently in terms of energy and time without damaging the sago flour.